Development of mitochondrial DNA typing method for human identification - Ishar, Seri Mirianti (2018)
Detection of mutations in human mtDNA is useful for the purpose of medical reports, molecular genetic analysis, haplogroup variations, forensic search and many other applications. In this project, Single Nucleotide Polymorphims (SNPs) from coding and control regions of mtDNA were selected for development of mtDNA typing kit. The main objective of this kit is to provide a simple, cost effective yet robust identification of human remains. A total of 30 SNPs that are specific for Southeast Asian haplogroups such as M, B, F, E and N were selected. The first round Polymerase Chain Reaction (PCR) was performed using 25 sets of in house designed primers. The purified amplified products were used in second round PCR known as allele specific PCR (asPCR) and also sent for sequencing to confirm the sequence of the amplified products. In asPCR, two types of allele specific primers (ASPs) for wild type ASP (wtASP) and variant type ASP (vtASP) were designed to identify the polymorphisms within the target fragments. A total of 20 ASPs were successfully designed and able to amplify the targeted SNPs. For quality control purpose and also to avoid false positive or false negative results in asPCR, an internal positive PCR control (IPC) was developed and incorporated together in the same tube during asPCR. A validation study for this mtDNA typing kit was carried out using human DNA samples (Malay, Chinese and Indian), mammals, insects and several types of bacteria. Sensitivity study was carried out using DNA extracted from ancient bones and serial dilution of freshhuman DNA sample. The ASPs are only specific for human DNA as no amplification was observed when using DNA template from other species. Based on the sensitivity validation study, the minimum amount of genomic DNA template required for optimum amplification of first round PCR is 1ng/μl. Based on the successful amplifications of both round PCRs using in house designed primers and the validation studies results, a simple yet effective mtDNA typing kit for human identification has been successfully developed in this study. This kit would be very much useful to narrow down individual classification especially in cases of mass disaster, forensic crime and plane crash.